Branch's elements of shipping / Alan E. Branch and Michael Robarts - Branch, Alan E.; Robarts, Michael (Routledge, 2014)
Since it was first published in 1964, Elements of Shipping has become established as a market leader. Now in its ninth edition, Branch's Elements of Shipping, renamed in memory of Alan Branch, has been updated throughout and revised to take in the many changes that have occurred in the shipping industry in recent years, including the impact of the economic crisis, the Panama Canal expansion and new legislation. All tables and data have been brought up-to-date and many new illustrations have been added. The book explains in a lucid, professional manner the basic elements of shipping, including operational, commercial, legal, economic, technical, managerial, logistical and financial considerations. It also explores how shipping markets behave and provides an overview of the international shipping industry and seaports. Filling a gap for the discerning reader who wishes to have a complete understanding of all the elements of the global shipping scene together with the interface with seaports, international trade and logistics, it remains essential reading for shipping executives along with students and academics with an interest in the shipping industry.